Leakage current energy harvesting application in a photovoltaic (PV) panel transformerless inverter system - Khan, Md Noman Habib; Khan, Sheroz (The Korean Institute of Electrical and Electronic Material Engineers, 2017)
Present-day solar panels incorporate inverters as their core components. Switching devices driven by specialized power controllers are operated in a transformerless inverter topology. However, some challenges associated with this configuration include the absence of isolation, causing leakage currents to flow through various components toward ground. This inevitably causes power losses, often being also the primary reason for the power inverters’ analog equipment failure. In this paper, various aspects of the leakage currents are studied using different circuit analysis methods. The primary objective is to convert the leakage current energy into a usable DC voltage source. The research is focused on harvesting the leakage currents for producing circa 1.1 V, derived from recently developed rectifier circuits, and driving a 200 Ω load with a power in the milliwatt range. Even though the output voltage level is low, the harvested power could be used for charging small batteries or capacitors, even driving light loads.